On one limit for convex monotone functions on M [0,1] - Surgailis, D. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Сургайлис. Об одном пределе для выпуклых монотонных функций на M [0,1] D. Surgailis. Apie vieną ribą iškiloms monotoniškoms funkcijoms, apibrėžtoms aibėje M [0,1]